Intraoperative Progress Reports to Families of Surgical Clients: A Missed Opportunity - Puopolo, Rose; Cordasco, Julie (Operating Room Nurses Association of Canada Journal, 1999)
The wait while a family member or loved one is undergoing surgery is stressful and anxiety- producing. Perioperative nursing contact during this period can result in positive outcomes of decreased anxiety, increased receptivity to post- operative information, and increased awareness of the professional practice. Perioperative nurses have the skills and the opportunity to provide progress reports to the client’s family, at least once during surgery. Characteristics important to this role include motivation and commitment to be informative; caring; sensitivity and perceptivity; sense of humour; and education. Possible barriers to intraoperative communications include various lacks — of time; attention (related to monitoring requirements in the operating room); support from management, peers, and doctors; and therapeutic communication skills to alleviate anxiety. Progress reports to the family can decrease their physical stress and add to their satisfaction with the hospital.